(untitled) (Journal of Contemporary Studies, 2015)
Abstract The paper identifies significant fault-lines both within the policy making and policy implementation which obstruct the much desired virtue of national harmony and integration in Pakistan. Normally, it appears that most of the federating units, socio-cultural entities and groups offer a very strong sense of nationalism and patriotism with the state of Pakistan but there are some gray areas which need serious consideration. Nevertheless, a level of uneasiness and frustration on the part of some groups and units in respect of the mode and method of governance and policy directions can be felt in one way or another. For example, Balochis, Sindhis, Saraikis of South Punjab, and Pakhtuns question the policies of federation and seek their due shares and rights as enshrined in the constitution of Pakistan. The history of the centre-province relations in Pakistan does contain some bitter memories, where the rights of the smaller provincial unites were compromised and subjugated in favour of the stronger entity. It’s high time tolearn some lessons from the past and lead the process of nation-building and integration by taking such steps in policy-making which may help bring the fragmented pieces together cementing a stronger, prosperous and integrated Pakistan.